MENINGKATKAN HASIL BELAJAR TEMATIK PADA TEMA 7 KURIKULUM 2013 MELALUI MODEL INKUIRI TERBIMBING KELAS V SDN 24 SUMPUR KUDUS KECAMATAN SUMPUR KUDUS - Yusriati, Yusriati (Jurnal Manajemen Pendidikan, 2019)
The low student learning outcomes in thematic learning in class V on theme 7 of the 2013 curriculum is due to teacher learning methods that are less effective with dominant lectures. To overcome this problem the teacher uses a guided inquiry learning model in the 2013 curriculum thematic learning in class V on theme 7. This type of research is class action research, the research procedure consists of: planning, implementation, observation, and reflection stage. The research data was obtained with the results of the written test and using teacher and student observation sheets. The research subjects were first grade students of SDN 24 Sumpur Kudus, Sumpur Kudus Subdistrict, Sinjunjung Regency, in the second semester of the year 2017/2018 as many as 21 people. The results showed that the guided inquiry learning model could improve 2013 curriculum thematic learning outcomes in class V on theme 7 with completeness in the knowledge aspect of cycle I 72%, the value of social attitudes in the first cycle had good criteria and the value of skills aspects in the first cycle had good skills. The implementation of teacher activities in teaching with the guided inquiry learning model cycle I 83% was carried out and the activity of students in learning 77%. After being reflected, there was an increase in the second cycle with the completeness value of knowledge aspects 93%, aspects of social attitudes were very good and the aspects of skills were very good. In observing teacher activity it increased to 98% and student activity increased to 95% of active students. From the research analysis it can be concluded that the guided inquiry learning model can improve the 2013 curriculum thematic learning outcomes in class V on theme 7 of SDN 24 Sumpur Kudus, Sumpur Kudus District, Sinjunjung District